TAVR in patients with cardiogenic shock or severely decompensated aortic stenosis. (2nd May 2022) - Steffen, J; Stocker, A; Scherer, C; Haum, M; Fischer, J; Theiss, H; Braun, D; Rizas, K; Peterss, S; Massberg, S; Orban, M; Deseive, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Severe aortic stenosis (AS) can result in cardiogenic shock (CS) or severe cardiac decompensation. Although transcatheter aortic valve replacement (TAVR) is the routine procedure for elderly or inoperable patients with severe AS, its role as an emergency therapy for critically ill patients, especially due to CS, needs further investigation. Purpose: The purpose of this study was to explore clinical characteristics and long-term survival of patients treated with emergency TAVR. We hypothesised that patients surviving the initial interventional and intensive care treatment would have a similar prognosis as elective TAVR patients. Methods: All patients undergoing TAVR at our centre between 2013 and 2019 were screened for emergency TAVR or treatment on intensive care units (ICU) before TAVR. Selected patients were divided into groups with or without CS, defined as systolic blood pressure <90 mmHg or the use of inotropes and lactate >2 mmol/l. The remaining patients undergoing elective TAVR served as a comparison cohort. Results: Out of 189 patients with emergency TAVR, 53 patients were in CS (shock group) and 136 patients did not fulfil CS criteria (urgent group). Patients in the shock group were more often male (75.5% vs. 56.6%, p=0.02), had a higher Society of Thoracic Surgeons score (15.6 [IQR, 7.7-30.5] vs. 5.4 [3.8-8.3], p<0.01), and lower left-ventricular ejection fraction (38.0% vs. 48.0%, p<0.01). The rate of coronary artery disease was similar (78.0% vs. 75.2%, p=0.69). Concerning the cause of acute decompensation, a specific condition which resulted in a clinical deterioration triggering hospitalisation could be identified in most patients. These included, among others, volume overload, acute coronary syndromes, arrhythmias, infections, and bleeding. Before TAVR, patients were treated on an ICU for 3 [2-5] days (shock group) and 2 [1-5] days (urgent group), p=0.01. In the shock group, mechanical ventilation was more frequent (52.8 vs. 14.7%, p<0.01), and more patients received valvuloplasty before TAVR (18.9 vs. 3.7%, p<0.01). The Valve Academic Research Consortium 3 (VARC-3) composite endpoint of technical failure occurred more often in emergency patients (shock, 13.2% vs. urgent, 9.6%) than in the 2, 741 patients after elective TAVR (4.8%, p<0.01). Estimated 2-year mortality was higher in the shock compared to urgent group (hazard ratio, 2.1 [1.3-3.3], p<0.01). In a landmark analysis from day 90, 2-year mortality in these groups was comparable to elective TAVR patients (p=0.41, Figure). Conclusions: TAVR in CS is associated with increased mortality compared to other cases of urgent TAVR. Procedural complication rates exceed those of elective TAVR patients. However, patients treated with emergency TAVR who survived 90 days after the procedure had a prognosis similar to elective TAVR patients.